Proceedings of the 20th Congress of the International Ergonomics Association (IEA 2018). Auditory and vocal ergonomics, visual ergonomics, psychophysiology in ergonomics, ergonomics in advanced imaging / Volume X, ([2018]) - Unknown
No abstract available